Studi tentang Peta Kendali p Tentang Kualitas yang Distandarisasi untuk Proses Pendek - Narwati Narwati (Jurnal Ilmiah Dinamika Teknik, 2008)
Attribute control charts especially p charts have been used widely for statistical process of atribute characteristics. In many applications, however it is neither possible nor practical to obtain sufficient subgroups io estimate accurately the control limits for the conventional p chart. This may occur when the production process is characterized as being a short run. One short run situation is a production run which produces items in a short period of time. In this article we describe the standardized p chart that the beyond control limit probabilities of proposed chart